THE RELEVANCE OF A COMPREHENSIVE ANALYSIS OF MEDICAL AND DEMOGRAPHIC PROBLEMS IN CONNECTION WITH THE HARMFUL EFFECTS ON HUMANS OF ENVIRONMENTAL FACTORS IN KUZBASS - Андрей Георгиевич Петров; Виктор Андреевич Семенихин; Ольга Владимировна Хорошилова; Сергей Николаевич Филимонов; Юлия Александровна Сашко (Медицина в Кузбассе)
The goal is to identify patterns of changes that have occurred with medical and demographic indicators in connection with the harmful effects on humans of environmental factors in Kuzbass.